Acute appendicitis with normal total leukocyte count. - Jamaluddin M; Hussain SMA; Ahmad H (Department of Surgery, UKM Medical Centre, 2013)
The objective of this study was to ascertain whether acute appendicitis can occur in patients with a normal leukocyte count. This study was prospective and descriptive. In this study, patients of all ages coming to this hospital with pain in the right iliac fossa with duration less than seven days were included. All patients were clinically assessed for signs and symptoms of acute appendicitis and haemoglobin (Hb) %, total leukocyte count (TLC) count, Urine D/R and ultrasound of abdomen was observed. Patients having increase total leukocyte count, diabetic patients, patients with lump in the right lower quadrant and patients with hepatitis B and C reactive were excluded from this study. A diagnosis of acute appendicitis was made and patients were prepared for appendicectomy in emergency and appendicetomies done, per-operative findings were recorded and specimen sent for histopathology. This study included fifty patients of acute appendicitis with normal leukocyte count in which 56% of patients were male and 44% of patients were female. The minimum age of the patient was five years and maximum was 67 years with a mean age 20.32 years. Majority of patients had pain less than three days of duration while only 8% had pain duration more than four days. Ultrasound showed 26% of patients having normal appendix while 74% had inflamed appendix. A total of 6% of patients had no signs of inflammation on naked eye appearance per operatively, 12% had minimal signs of inflammation while 82% of patients had moderate to severe signs of inflammation. Histopathology showed 2% of patient had non-inflammatory appendix, 10% had minimal inflammation, and 72% had moderate inflammation while 16% had severe inflammation. Patients having signs and symptoms of acute appendicitis may have a normal total leukocyte count. The diagnosis of acute appendicitis is mainly clinical not laboratory based. So minimum investigations should be done in cases of acute appendicitis where clear signs and symptoms of acute appendicitis are present, in order to avoid delay in surgery and save costs involved.